Efecto del diseño de intercambiadores de placas basado en la eficiencia de transmisión de calor en la simulación de procesos de pasteurización de jugos y bebidas de frutas. - Ramón Mimbela, Jaime Erick (2012)
It has used a computer program to analyze pasteurize bottled fruit drinks cold or hot, in plate heat exchangers. The program consists of configuration modules, microbiology, calculation of thermal processes, process simulation and production. With product composition data in study, flows and temperatures means heating and cooling, the product flow conditions as well as their temperature profiles are estimated. With this information and the application of the general method sterility levels (F values) are achieved in each case they were estimated. The inclusion of data on the kinetics of destruction of microorganisms, development of flavor in products and process costs, can generate the optimal conditions with which ensures sterility of the product, its deterioration and the cost of the process is minimized.